Pemanfaatan YouTube sebagai Media Pembelajaran Vokal Pop Jazz di Prodi Pendidikan Musik Institut Seni Indonesia Yogyakarta - Suryati, Suryati (Resital: Jurnal Seni Pertunjukan, 2021)
Utilizing Youtube as a Learning Media for Pop-Jazz Vocal Course at Music Education Study Program of Institut Seni Indonesia Yogyakarta. The research aims to reveal the learning process of the Pop-Jazz vocal course and the utilization of youtube as an accompaniment in learning the Pop- Jazz vocal course. This research is expected to provide solutions for students who face problems in the learning process of the Pop-Jazz vocal course during the covid-19 pandemic. It is qualitative research with a case study approach. Data collection techniques were carried out through direct observation during the learning process. Furthermore, interviews with teachers and vocal students of Pop-Jazz were conducted to obtain the data. It was a case study of vocal students of Pop-Jazz Intermediate 1 at the Music Education Study Program. The literature studies were carried out to support the data and references. This study shows that the interest in vocal learning of Pop-Jazz at the Music Education Study Program by utilizing youtube as an accompaniment at the pop-jazz vocal course can be increased.